OP0054 Neuroimmunomodulation of Neutrophils as A Novel Mechanism of Levamisole-Induced Vasculitis. (15th July 2016) - Grayson, P.C.; Carmona-Rivera, C.; Graf, J.; Irizarry-Caro, J.; Phillips, K.; Preston, K.; Purmalek, M.; Subramaniam, V.; Thompson, P.; Waldman, M.; Kaplan, M.J.
Abstract : Background: Levamisole, an anti-helminth drug and known cholinergic agonist, has been implicated in cases of drug-induced autoimmunity in humans exposed to cocaine adulterated with levamisole for profit. Clinical manifestations of levamisole-induced autoimmunity include cutaneous vasculitis and specific autoantibodies (e.g. anti neutrophil cytoplasmic antibodies, ANCA; antinuclear antibodies, ANA). Neutrophil extracellular trap (NET) formation is a novel cell death mechanism implicated in certain idiopathic autoimmune diseases that share features with levamisole-induced autoimmunity. Objectives: The objective of this study was to determine the role of NET formation in the pathogenesis of levamisole-induced autoimmunity. Methods: Human and mouse neutrophils were exposed to graded concentrations of levamisole. NET formation was visualized and quantified by fluorescence microscopy. To assess the pathways involved in levamisole-induced NETosis, the following inhibitors were tested: diphenylene iodonium (DPI), an inhibitor of reactive oxygen species, and Cl-amidine, an inhibitor of peptidylarginine deiminase (PAD) enzymes. Involvement of Akt and Raf-MEK-ERK kinase pathways was assessed by Western blot. The role of Toll-like receptors (TLRs) and muscarinic receptors (MR) in levamisole-induced NETosis was investigated. Pharmacologic inhibitors and MR knockout mice were used to study specific MR subtypes implicated in NETosis. MR subtype receptors on neutrophils from disease comparators and healthy controls were assessed by flow cytometry. Autoantibodies against specific NET-components were examined in cocaine users exposed to levamisole. Results: Levamisole induced prominent NETs in human and murine neutrophils that contained the antigenic targets of ANCA. NETs were seen in vasculitic lesions from cocaine/levamisole users. NET formation induced by levamisole was dependent on phosphorylation of Akt and Raf-MEK-ERK kinase pathways. DPI and Cl-amidine significantly abrogated levamisole-induced NETosis, highlighting that levamisole stimulates NETs via generation of reactive oxygen species and activation of PAD enzymes. Both levamisole and acetylcholine induced NETs through MR engagement on the surface of neutrophils and not through stimulation of TLRs. Atropine, a non-selective MR antagonist, blocked levamisole mediated NETosis. Screening experiments with pharmacologic inhibitors and neutrophils from MR knockout mice demonstrated that levamisole-induced NETosis was mediated through engagement of the M3 muscarinic receptor. Increased M3 receptors were seen on neutrophils from patients with systemic lupus erythematosus compared to controls. In a cohort of 21 cocaine users, 100% had quantifiable levamisole in urine, and novel autoantibodies against NET components were detectable in sera. In longitudinal observations, ex-vivo spontaneous NET formation correlated with periods of active cocaine use. Conclusions: Levamisole induces NETosis through engagement of M3 muscarinic receptors on the surface of neutrophils. These findings implicate a novel interaction between the cholinergic nervous system and innate immunity in the pathogenesis of levamisole-induced autoimmunity. Disclosure of Interest: None declared